Entre “rejeitos”, riscos e resíduos: perspectivas e desafios no gerenciamento de resíduos em hospitais públicos do Estado do Pará - GOMES, Jocileide de Sousa (Universidade Federal do Pará, 2017)
The Waste of Health Services, especially hospital waste, are configured in important object of analysis because they involve complex environmental issues that dialogue with the challenging relationship consumption and environmentally proper disposal and, above all, minimizing the potential risks to environmental health, occupational and collective. Considering the normative instrument which guides its actions for sustainability in the management of this waste, this thesis aimed to identify the prospects and challenges the Commission's public three hospitals Waste Management from Pará State in attending to what is established legally. With technical, methodological tools for data analysis and field research and documentary, interviews and participant observation, evidence of political, social, economic and technical fragility between the members responsible for minimization, reuse, recycling and disposal of waste generated environmentally by their respective hospitals. From the analytical contributions of theoretical and methodological framework used, it was found that the economic interest together with the rejection of the changes demanded by the waste management outnumber the interests focused on the prevention and reduction of risks they may pose to global health. The identification of watering "beyond gaming" also allowed strip that waste management visibility and effectiveness is only achieved when there is commitment to the interest to go along with the social and environmental perspective that the subject requires.